Eye-tracking Analysis of the Ergonomics of an Internet-based Educational Portal in the Acceptance Testing Process - Wawer, Rafał Ireneusz (Journal of Education, Technology and Computer Science, 2021)
In the article I will present the concept of using eye-tracking to examine the ergonomics of operating an Internet educational portal in the acceptance testing process. In the test performed, the results were obtained in nine sections characteristic of the defined AOI1 vs. REC. Selected data has been presented as an example of the results obtained from a complete study showing how users browse the content of the primary conclusion is the way of arranging information on the home page. Permanent arrangement of information takes the form of a non-editable menu. This is the most popular solution found, because it allows for permanent unity of content and easy search. 1. Coherence is located in the context of logical substantive integration. 2. Communication is measured by measuring average time viewed, fixations and number of revisits to defined areas.